ABCA1- and ABCG1-mediated cholesterol efflux capacity of cerebrospinal fluid is impaired in Alzheimer’s disease - Marchi, Cinzia (J Lipid Res, 2019)
HDL-like particles in human cerebrospinal fluid (CSF) promote the efflux of cholesterol from astrocytes toward the neurons that rely on this supply for their functions. We evaluated whether cell cholesterol efflux capacity of CSF (CSF-CEC) is impaired in Alzheimer’s disease (AD) by analyzing AD (n = 37) patients, non-AD dementia (non-AD DEM; n = 16) patients, and control subjects (n = 39). As expected, AD patients showed reduced CSF Aβ 1-42, increased total and phosphorylated tau, and a higher frequency of the apoε4 genotype. ABCA1- and ABCG1-mediated CSF-CEC was markedly reduced in AD (−73% and −33%, respectively) but not in non-AD DEM patients, in which a reduced passive diffusion CEC (−40%) was observed. Non-AD DEM patients displayed lower CSF apoE concentrations (−24%) compared with controls, while apoA-I levels were similar among groups. No differences in CSF-CEC were found by stratifying subjects for apoε4 status. ABCG1 CSF-CEC positively correlated with Aβ 1-42 (r = 0.305, P = 0.025), while ABCA1 CSF-CEC inversely correlated with total and phosphorylated tau (r = −0.348, P = 0.018 and r = −0.294, P = 0.048, respectively). The CSF-CEC impairment and the correlation with the neurobiochemical markers suggest a pathophysiological link between CSF HDL-like particle dysfunction and neurodegeneration in AD.